Perception Of Students In Using Youtube On Learning English - Neneng Islamiah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2021)
The aim of this research was to know perception of watching English movie on Youtube at the second semester the second semester of English department Islamic University of Kalimantan of the 2018/2019 academic year. The subject of this research is the students of class regular A. The instrument used in the data collection was a questionnaire that consist of two part, the first part to find out the students who ever watched English movie on Youtube and the second part to know students’ perception use of watching English movie on Youtube. The data were analyzed using statistical  and shown in tables of frequency.The finding showed that by watching English movie on Youtube English  movie has an influenced for those students in improving their English achievement, then  help them to learn new vocabulary and could be one of  the effective  media in learning English Achievement.  Keywords : learning english, English movie, Youtube